Factors of Entrepreneurial Intention Among Students in Indonesia - Muchtadin; Nurul Sukma Lestari (MultiTech Publisher, 2022)
The research aims to determine the extent to which subjective norms influence students' entrepreneurial intentions through the mediation of entrepreneurial attitudes, perceptions of behavioral control, and opportunity recognition. Respondents were 149 students aged 17 to 25 years. Sampling was done by accidental sampling. PLS SEM is used as a data analysis method. The results of the study found that subjective norms did not have a direct effect on entrepreneurial intentions. Subjective norms will have a positive impact on entrepreneurial intentions if through the mediation of entrepreneurial attitudes, perceived behavioral control, and opportunity recognition. This research contributes to efforts to increase students' entrepreneurial intentions in Indonesia through increasing entrepreneurial attitudes, perceived behavioral control, opportunity recognition and subjective norms